The effect of job displacement on the transitions to employment and early retirement for older workers in four European countries - Konstantinos Tatsiramos (Institute for the Study of Labor (IZA), 2007)
Despite the increased frequency of job loss for older workers in Europe, little is known on its effect on the work-retirement decision. Employing individual data from the European Community Household Panel for Germany, Italy, Spain, and the U.K., a multivariate competing-risks hazard model is estimated in which the effect of job displacement is identified separately for transitions into re-employment and retirement. The findings suggest that in countries with institutional provisions for older unemployed which offer a pathway to early retirement such as, Germany and Spain, older displaced workers exhibit lower re-employment and higher retirement rates compared to the non-displaced. These results are robust to dynamic selection due to unobserved heterogeneity and to the endogeneity of displacement.
Keywords: 330; Job displacement; job loss; unemployment duration; retirement; competing risks; Personalabbau; Arbeitslosigkeit; Dauer; Ältere Arbeitskräfte; Flexible Altersgrenze; Berufliche Integration; Deutschland; Italien; Spanien; Großbritannien